Effect of Xylitol, Sorbitol, and Combination Xylitol-Sorbitol Chewing Gum on Increasing Saliva pH - WIJAYA, DHANDI; HAMID, ABU; ISMALAYANI, ISMALAYANI (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2023)
Saliva is an important factor in maintaining dental and oral health which plays a role in protective functions. The protective function is carried out by increasing saliva secretion which can be measured through flow speed, volume, pH and viscosity. The aim of this study is to determine the effect of chewing gum containing xylitol, sorbitol, and a combination of xylitol-sorbitol on increasing saliva pH. This research is a quasi-experiment research carried out in March 2022 at the Dental Health Program Study of Health Polytechnic of Palembang. The research sample of 60 people from the Dental Health Department was grouped into three groups. Each group was treated with chewing gum containing two pieces of xylitol, sorbitol, and a combination of xylitol-sorbitol for five minutes. Saliva measurements are carried out using a pH meter. Data were analyzed using a one-way anova test with a 95% confidence interval. The mean salivary pH in each group showed a significant increase (p<0.05). OnThe group that chewed gum containing xylitol had an increase in the mean saliva pH of 1.839, in the group that chewed gum containing sorbitol there was an increase in the mean saliva pH of 1.698, and in the group that chewed gum containing a combination of xylitol-sorbtiol there was an increase in the mean saliva pH of 1.868. There was a significantly increase in the mean pH of saliva in the three groups of subjects after chewing gum (p<0.05), but no significant mean differences were found between treatment groups (p>0.05). Chewing gum containing xylitol, sorbitol, and a combination of xylitol-sorbitol can reduce the risk of dental caries by increasing saliva pH.